KOMPARASI PENERAPAN TEORI BRUNER DAN VAN HIELE PADA PEMBELAJARAN MATEMATIKA SISWA SEKOLAH DASAR - Suhartini, Siti; Rosnita, Margiati; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the presence or absence of differences in the average student learning outcomes in learning mathematics by using learning theory Bruner and Van Hiele in class III Pontianak City Elementary School 03. The method used is an experimental method. In this study, using Quasi Experimental Design with the Nonequivalent Control Group Design form. The population in this study were all third grade students of Public Elementary School 03 Pontianak City, while the sample was obtained through drawing in all class III. Based on the results of the draw, obtained a sample of research namely class III A (experimental class 1) and III B (experimental class 2) totaling 64 students. Data collection techniques used are measurement techniques and data collection tools are multiple choice written tests. Based on data analysis, the average post-test results of experimental class 1 were 75.71 and the average post-test experimental class 2 was 69.17. Hypothesis test results using t-test (Polled Variance) obtained t count = 2.161 while for dk (31 + 33 - 2 = 62) with a significant level α = 5% obtained t table = 1.667, which means thitung> t table, then Ha is accepted, this prove there is a significant difference between student learning outcomes in learning mathematics by applying Bruner's learning theory and Van Hiele's in class III Pontianak City Elementary School 03. Keywords: Comparation, Van Hiele's Learning Theory, Bruner's Learning Theory, Mathematics Learning, Learning Outcomes.